PENGEMBANGAN KAPASITAS SUMBER DAYA MANUSIA KOPERASI SYARIAH BERBASIS MASJID DI KOTA BANDUNG - Ali, Muhammad; Ikram, Syafrizal; Suryana, Suryana; Arnan, Sendi Gusnandar (Jurnal AbdiMas Nusa Mandiri, 2025)
Mosque-based sharia cooperatives are increasing in number in Bandung City. The problem faced by mosque-based sharia cooperatives is the limited capacity of human resources to prepare integrated and up-to-date sharia cooperative financial reporting. Many managers of sharia cooperatives do not have the skills to prepare financial reports based on sharia accounting standards needed to meet job demands. In addition, the lack of training programs is an obstacle to the ability of cooperative managers because training programs require costs for human resource development so that managers can meet the expected standards. Managers also have difficulty adapting to the development of accounting application technology, which can reduce the competitiveness of cooperatives in the business environment. This community service aims to provide management with knowledge about preparing financial reports that comply with standards and how to implement financial accounting for sharia cooperatives in the city of Bandung. The software used is Accurate. Accurate was developed with the aim of continuing to provide ease of financial recording with PSAK standards for various types of businesses from MSMEs to large companies. This activity was carried out by a group of lecturers from the Bachelor of Accounting study program at Widyatama University in collaboration with the economics sector of the Bandung City MUI and the mosque cooperative center. The implementation method is carried out in four stages, namely preparation, training, evaluation and reporting, and mentoring. The administrators of sharia cooperatives feel they have gained direct knowledge of the subject matter so they are able to prepare sharia cooperative financial reports based on sharia accounting standards.